Subjective Well-Being of Tarim Women: A Study of Asceticism in the Novel "Bidadari Bumi" (Bidadari Bumi) - Nur Chamidah (Feelings: Journal of Counseling and Psychology, 2026)
This study examines the subjective well-being of Tarim women as reflected in Halimah Alaydrus's novel "Bidadari Bumi" (Bidadari Bumi) using Ed Diener's subjective well-being theory and Max Weber's concept of asceticism. Using a qualitative descriptive research method, this study aims to uncover how Tarim women's subjective well-being is represented in contemporary literature and to analyze its relationship to the values ​​of asceticism that are an integral part of Tarim society. Data were obtained through a close reading of the novel, focusing on the narrative and dialogue depicting the emotional experiences, life satisfaction, and religious practices of the female characters. The results indicate that Tarim women's subjective well-being is formed through a complex interaction between life satisfaction based on spiritual values, positive affect stemming from religious devotion, and internalized ascetic practices in daily life. These findings provide a new perspective on how traditional values ​​and modernity can coexist in shaping women's psychological well-being in the context of a traditional Muslim society.